(untitled) (Applied Research and Innovation, 2023)
The construction industry is one of the largest producers of greenhouse gases and waste materials. One potential solution to reduce the environmental impact of construction is to use sustainable materials in the production of concrete. The effects of adding low-density polyethylene (LDPE) waste and stone dust on the mechanical properties of the 7-days cured composite materials adopting two independent categorical variables with five levels each, creating 25 groups were investigated. The dependent variables are compressive strength, tensile strength, flexural strength, and water absorption. The results show that increasing LDPE waste content and stone dust content improves the mechanical strength of the composite material but increases water absorption. The optimal combination of LDPE waste content and stone dust content is 30% LDPE waste and 40% stone dust, based on the highest values of compressive, tensile, and flexural strength and the lowest value of water absorption in the group. It also provides linear regression models and correlation analysis to determine the relationships between LDPE waste content and each dependent variable. On this basis, it suggests that LDPE waste can improve the mechanical properties of the composite material and its water resistance, but the optimal amount of LDPE waste depends on the type of material and application. The study concludes that incorporating LDPE waste and stone dust into composite materials can be a sustainable solution for waste management and the production of low-cost, high-performance materials.